2020
DOI: 10.1029/2019jc015886
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Breaking Onset Criterion for Surface Gravity Water Waves in Arbitrary Depth

Abstract: We investigate the validity and robustness of the Barthelemy et al. (2018, https://doi.org/10.1017/jfm.2018.93) wave‐breaking onset prediction framework for surface gravity water waves in arbitrary water depth, including shallow water breaking over varying bathymetry. We show that the Barthelemy et al. (2018) breaking onset criterion, which they validated for deep and intermediate water depths, also segregates breaking crests from nonbreaking crests in shallow water, with subsequent breaking always following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 62 publications
(83 reference statements)
1
77
0
Order By: Relevance
“…Physical velocities expressed at fixed z elevations would be found by determining the σ value at the desired z and local values of h(x) and η(x, t), after which the horizontal velocity in physical coordinates is given by u = u α + ∇φ 2 σ (z) 2 + 2σφ 2 ∇σ . On the other hand, the model described here provides a natural setting for determining quantities at the free surface, as in, for example, the determination of wave breaking criteria based on values of the horizontal particle velocity at the free surface (Barthelemy et al 2018;Derakhti et al 2020). We conclude that trough instability is not an intrinsic feature of FNBTE and can be eliminated by derivations that produce equations with total layer depth as the only measure of layer thickness in dispersive term coefficients.…”
Section: Discussionmentioning
confidence: 87%
“…Physical velocities expressed at fixed z elevations would be found by determining the σ value at the desired z and local values of h(x) and η(x, t), after which the horizontal velocity in physical coordinates is given by u = u α + ∇φ 2 σ (z) 2 + 2σφ 2 ∇σ . On the other hand, the model described here provides a natural setting for determining quantities at the free surface, as in, for example, the determination of wave breaking criteria based on values of the horizontal particle velocity at the free surface (Barthelemy et al 2018;Derakhti et al 2020). We conclude that trough instability is not an intrinsic feature of FNBTE and can be eliminated by derivations that produce equations with total layer depth as the only measure of layer thickness in dispersive term coefficients.…”
Section: Discussionmentioning
confidence: 87%
“…For the data investigated here, such underestimation did not result in a high mean absolute error (MAE) and, in fact, our model had one of the lowest MAE. Recent results of Barthelemy et al (2018), Derakhti et al (2020) and Varing et al (2020) showed that waves with horizontal fluid velocity that exceeds 0.85 times the phase velocity will inevitably break. These results suggest that the breaking threshold derived from Cokelet (1977) in Section 2.3 could be reduced by ≈15%.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Barthelemy et al (2018) found and Derakhti et al (2020) confirmed via numerical simulations that waves will inevitably start to break shortly after u c exceeds 0.85 in deep and shallow water. Further numerical simulations showed that wave breaking occurs when the maximum orbital velocity (u max ) equals c somewhere along the wave profile and not necessarily at the wave crest (Varing et al, 2020).…”
Section: Definition Of a Probabilistic Wave Breaking Model Based On Gaussian Field Theorymentioning
confidence: 90%
See 1 more Smart Citation
“…For the data investigated here, such underestimation did not result in a high MAE and, in fact, our model had one of the lowest MAE. Recent results of Barthelemy et al (2018), Derakhti et al (2020), andVaring et al (2020) showed that waves with the horizontal fluid velocity that exceeds 0.85 times the phase velocity will inevitably break. These results suggest that the breaking threshold derived from Cokelet (1977) in Section 2.3 could be reduced by ≈15%.…”
Section: Discussionmentioning
confidence: 99%